Direito à advertência na legislação aeronáutica brasileira: medida de inclusão das pequenas empresas de serviço aéreo - Vollbrecht, Ricardo (Universidade do Vale do Rio dos Sinos, 2023)
ANAC, with the Responsive Regulation Project, proposes to rethink its current regulation model, to use command and control tools only when strictly necessary. However, the research faces the problem that, in the case of small airlines in the aeroagricultural sector, which are served by SINDAG, with legal advice from the researcher, the conduct of ANAC remains in supervising and punishing with fine, suspension and cassation without conferring on small companies the right to responsive regulation through the warning, reflecting in the research question: How would it be feasible to implement the warning with an institutional character for the inclusion of small aeroagricultural companies in regulatory compliance? The research has as general objective to contribute to the implementation of the Responsive Regulation Project of ANAC and as a hypothesis, the institutionalization of the warning, with a positive and inclusive legal nature. To achieve this goal, the following specific objectives are: (i) to map the context of structure and operation of small airlines in Brazil; (ii) demonstrate the absence of differential constitutional treatment between small and large airlines regulated by ANAC based on penalties; and (iii) present the institutional warning as an inclusive regulatory process in the pursuit of appropriate compliance by small businesses. The methodology is descriptive and hypothetical-deductive, since it starts from the analysis of the situation of the regulation of small airlines by ANAC to conclude that the warning is an instrument capable of improving the communication between regulator and regulated. As the concern is with the effect of regulation in the inspection phase, the theoretical framework is the Economic Analysis of Law, the school of New Institutional Economics and the Theory of Responsive Regulation. As a result, the research presents the need to improve the pyramid of embarrassment of ANAC with the warning as an inclusive regulatory process in the search for adequate compliance by small companies, to favor the effectiveness of the intended responsive regulatory system. As research findings, ANAC, in the part of inspection and application of sanctions, continues to provide in resolutions such as punitive measures fine, suspension and cassation, not including the possibility of warning, thus reinforcing the evidence that the Public Administration remains repressive in case of nonconformities, regardless of the profile of the company.
Keywords: ANAC; Pequenas empresas; Regulação responsiva; Advertência; Direito regulatório; Small businesses; Responsive regulation; Warning; Regulatory right; ACCNPQ::Ciências Sociais Aplicadas::Direito